ANALYSIS OF ECONOMIC EFFICIENCY INDICATORS OF AGRIBUSINESS ENTITIES - Seyfullayeva, Ayzada Tolibekovna; Abishov, Mukhammed Sarsenbaevich (THE INNOVATION ECONOMY, 2026)
This article analyzes the role of investments in increasing the economic efficiency of agribusiness entities in the Republic of Karakalpakstan. Based on data for 2016–2024, an econometric assessment of the relationship between agricultural investments and gross agricultural output was conducted using the STATA software. Trend, correlation, and regression models statistically substantiate the impact of investments on production volume, employment, and export potential. In addition, the experiences of the Netherlands, China, and Kazakhstan are analyzed, and scientific and practical recommendations for the development of agribusiness in the region are proposed. The results show the necessity of increasing investment activity, developing agro-clusters, and strengthening public-private partnership mechanisms.